Internal quantum efficiency mapping for evaluation of rear surface of passivated emitter and rear cell. (9th July 2018) - Mochizuki, Toshimitsu; Joonwichien, Supawan; Tanahashi, Katsuto; Shirasawa, Katsuhiko; Sakata, Isao; Takato, Hidetaka
Abstract: An internal quantum efficiency (IQE) mapping method that can emphasize the effects of local structures on the rear side of solar cells is demonstrated. The IQE of crystalline silicon passivated emitter and rear cells was mapped at 1000 nm and revealed periodic patterns with lower IQE in the local aluminum back surface fields on the rear surface. A larger-scale map indicated an effect that is apparently related to the spin-etching process on the rear surface. The proposed IQE mapping method can provide information that will help identify the factors that limit the efficiency.